1987
DOI: 10.1136/bmj.294.6565.156
|View full text |Cite
|
Sign up to set email alerts
|

Sweat osmolality in Down's syndrome and cystic fibrosis in an Indian population.

Abstract: PI blockers who require a calcium antagonist for the treatment of angina are prescribed one that has no effect on cardiac conducting tissue.We thank Mrs Sheila Haugh for typing this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In this study, the healthy women had a mean sodium concentration of 62 mmol/1. This was in accor dance with a previous study of sweat osmolality in an Indian population which showed an upper limit of 160 mmol/kg, corresponding to about 65 mmol/1 sodium and potassium [4], That study showed no age correlation and somewhat higher values in women. O ur results were somewhat higher than the 25 mmol/1 chloride and sodium found by Davies et al [3] in healthy subjects with a mean age of 53 years, ranging from 18 to 85 years [3], 18% of the control women reported a diminished sweating ability.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…In this study, the healthy women had a mean sodium concentration of 62 mmol/1. This was in accor dance with a previous study of sweat osmolality in an Indian population which showed an upper limit of 160 mmol/kg, corresponding to about 65 mmol/1 sodium and potassium [4], That study showed no age correlation and somewhat higher values in women. O ur results were somewhat higher than the 25 mmol/1 chloride and sodium found by Davies et al [3] in healthy subjects with a mean age of 53 years, ranging from 18 to 85 years [3], 18% of the control women reported a diminished sweating ability.…”
Section: Discussionmentioning
confidence: 49%
“…In a previous study of 20 patients with Down's syn drome the mean sweat osmolality was 228 mmol/kg, cor responding to a sodium and potassium level of about 110 mmol/1 and similar to the mean value of 91 mmol/1 in our AD patients [4]. All patients in that study had values higher than 160 mmol/kg [4], Patients with Down's syn drome develop cognitive reduction and a dementia-like state in the 4th-6th decades.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations